2022
DOI: 10.1136/jmedgenet-2022-108490
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and behavioural features of Lowe syndrome and their potential molecular mechanisms

Abstract: BackgroundLowe syndrome (LS) is an X linked disease caused by pathogenic variants in the OCRL gene that impacts approximately 1 in 500 000 children. Classic features include congenital cataract, cognitive/behavioural impairment and renal tubulopathy.MethodsThis study is a retrospective review of clinical features reported by family based survey conducted by Lowe Syndrome Association. Frequency of non-ocular clinical feature(s) of LS and their age of onset was summarised. An LS-specific therapy effectiveness sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…There is no longer a problem with cryptorchidism, and additional surgery is not anticipated. Thus, it is not surprising that in a recent series of 137 patients, Sena et al showed that 15% of patients were favorably treated with rhGH [16].…”
Section: Discussionmentioning
confidence: 99%
“…There is no longer a problem with cryptorchidism, and additional surgery is not anticipated. Thus, it is not surprising that in a recent series of 137 patients, Sena et al showed that 15% of patients were favorably treated with rhGH [16].…”
Section: Discussionmentioning
confidence: 99%